2009
DOI: 10.1111/j.1365-2222.2009.03364.x
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐centre study of candidate genes for wheeze and allergy: the International Study of Asthma and Allergies in Childhood Phase 2

Abstract: Despite the biological plausibility of IgE-related mechanisms in asthma, very few of the tested candidates showed evidence of association with both wheeze and increased IgE levels. We were unable to confirm associations of the positional candidates DPP10 and PHF11 with wheeze, although our study had ample power to detect the expected associations of IL13 variants with IgE and SPINK5 variants with eczema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 29 publications
1
37
1
1
Order By: Relevance
“…if one parent is atopic there is a 20-40 % probability of a child developing this condition and, if both parents are atopic, a 50-80 % probability). Epidemiological studies are identifying genes involved in atopic predisposition (Walley et al, 2001;Weidinger et al, 2008;Genuneit et al, 2009). For example, filaggrin gene defects have recently been identified as a major risk factor for the development of atopic dermatitis.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…if one parent is atopic there is a 20-40 % probability of a child developing this condition and, if both parents are atopic, a 50-80 % probability). Epidemiological studies are identifying genes involved in atopic predisposition (Walley et al, 2001;Weidinger et al, 2008;Genuneit et al, 2009). For example, filaggrin gene defects have recently been identified as a major risk factor for the development of atopic dermatitis.…”
Section: Atopic Dermatitismentioning
confidence: 99%
“…AR is an inflammatory disease of the nasal mucosa induced by an immunoglobulin E (Helbling et al, 2014)-mediated reaction in allergen-sensitized individuals. It has been reported that numerous loci and candidate genes show an association with AR (Gaddam et al, 2012;Genuneit et al, 2009;Ibrahim et al, 2012;Tomazic et al, 2014). In spite of that, the molecular mechanisms underlying the development of AR have not been completely determined.…”
Section: Introductionmentioning
confidence: 95%
“…Allergic inflammation is characterized by airway hyperreactivity, type 2 cytokines (IL-4, -5, and -13), IgE, and the overproduction of mucus in the lung (1)(2)(3). Macrophages present at the site of allergic inflammation can be polarized by Th2-cytokines to become "alternatively activated" or M2 macrophages.…”
mentioning
confidence: 99%